2019
DOI: 10.1186/s12889-019-6462-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic pathways and delay among tuberculosis patients in Stockholm, Sweden: a retrospective observational study

Abstract: BackgroundAsylum seekers in Sweden are offered tuberculosis (TB) screening at a voluntary post-arrival health examination. The role of this screening in improving the TB diagnostic pathway has not been previously evaluated. The aim of this study was to determine diagnostic pathways for active TB cases and compare diagnostic delays between different pathways.MethodsRetrospective review of medical records of patients reported with active TB in Stockholm in 2015, using a structured and pre-coded form.ResultsSeven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Accounting appropriately for DR-TB in mathematical models of disease is critical, as it differs considerably from drug-sensitive TB (DS-TB) in both epidemiological parameters and relevant outcomes. Some variation in disease characteristics is relatively well-understood, including the prolonged treatment duration [ 7 ], adverse event rates [ 8 ] and diagnostic pathway performance [ 9 , 10 ]. However, considerable uncertainties persist regarding important characteristics of MDR-TB, including pathogen’s fitness, transmissibility and risk of resistance amplification related to treatment [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accounting appropriately for DR-TB in mathematical models of disease is critical, as it differs considerably from drug-sensitive TB (DS-TB) in both epidemiological parameters and relevant outcomes. Some variation in disease characteristics is relatively well-understood, including the prolonged treatment duration [ 7 ], adverse event rates [ 8 ] and diagnostic pathway performance [ 9 , 10 ]. However, considerable uncertainties persist regarding important characteristics of MDR-TB, including pathogen’s fitness, transmissibility and risk of resistance amplification related to treatment [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… 11 One study in Sweden reported that a TB screening programme targeting refugees only contributed to 15% of the total cases, suggesting that with this approach other migrant groups are missed, and they could be potentially targeted in other settings such as primary care. 12 In addition, moving from routine HIV testing from sexual health and antenatal clinics to non-traditional settings (e.g. primary care) to reduce the pool of undiagnosed HIV infection in the population is cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…Accounting appropriately for MDR-TB in mathematical models of disease is critical; as it differs considerably from drug-sensitive TB (DS-TB) in both epidemiological parameters and relevant outcomes. Some variation in parameters is relatively well-understood, including the prolonged treatment duration [7], adverse event rates [8] and diagnostic pathway performance [9,10]. However, considerable uncertainties persist with regards important characteristics of MDR-TB, particularly those relating to fitness, transmissibility and risk of resistance amplification related to treatment [11,12].…”
Section: Introductionmentioning
confidence: 99%